Diamagnetic depression observations at Saturn's magnetospheric cusp by the Cassini spacecraft. Issue 6 (27th June 2017) - Jasinski, Jamie M.; Arridge, Christopher S.; Coates, Andrew J.; Jones, Geraint H.; Sergis, Nick; Thomsen, Michelle F.; Krupp, Norbert
Abstract: The magnetospheric cusp is a region where shocked solar wind plasma can enter a planetary magnetosphere, after magnetic reconnection has occurred at the dayside magnetopause or in the lobes. The dense plasma that enters the high‐latitude magnetosphere creates diamagnetic effects whereby a depression is observed in the magnetic field. We present observations of the cusp events at Saturn's magnetosphere where these diamagnetic depressions are found. The data are subtracted from a magnetic field model, and the calculated magnetic pressure deficits are compared to the particle pressures. A high plasma pressure layer in the magnetosphere adjacent to the cusp is discovered to also depress the magnetic field, outside of the cusp. This layer is observed to contain energetic He ++ (up to ∼100 keV) from the solar wind as well as heavy water group ions (W + ) originating from the moon Enceladus. We also find a modest correlation of diamagnetic depression strength to solar wind dynamic pressure and velocity; however, unlike at Earth, there is no correlation found with He ++ counts. Key Points: Diamagnetic depressions are found in the cusp and are observed to continue into the adjacent magnetosphere A heated plasma layer of mixed composition is found to depress the adjacent magnetospheric field Diamagnetic depression strength is correlated to solar wind dynamic pressure and velocity but not to the observed He ++ counts, like at Earth